Synthesis and characterization of certain thiourea derivatives starting from 1,2,4-triazoline-3-thiones as potential antibacterial and antifungal agents - (:unkn) unknown (My University, 1995)
Several N-substituted-N’-[4-(4-alkyl/aryl-2,4-dihydro-3H-1,2,4-triazole-3-thione-5-yl)phenyl]thioureas were synthesized in order to examine their antibacterial and antifungal activities. The structures and purity of the synthesized compounds were confirmed by UV, IR and mass spectral data and elemental analysis. However, they were found not to possess significant antibacterial or antifungal activity. © Freund Publishing House, Ltd. 1995
Keywords: 1,2,4-triazoline-3-thione; agar diffusion method; antifungal activity; substituted thiourea